A importância de um índice de volatilidade para o mercado brasileiro - Moura, Gustavo Torres Cursino de (2011)
The purpose of this paper is to analyze the importance of an implied volatility index for the Brazilian market. Since it is thought of as a measure of market expectations, and due to the arrival of new economic data, some studies (mainly foreign) have been able to extract important information regarding changes in implied volatility. By analyzing interest rate options (IDI) and exchange rate options (Real/Dollar), this paper verifies whether macroeconomic data impacts volatility. The results show that a large range of such data affects interest rate expectations, whereas only central bank interventions through swap contracts cause an impact on the exchange rate market. Lastly, the study concludes that certain non-transactional variables explain the volatility variations, which shows that the implied volatility of options contain a significant amount of information on market expectations